Comparison of micronuclei frequency between smokers and non-smokers: a systematic review - Rodrigo B Andrade; Nadine Alessandra Campos (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: Cancer results from the accumulation of several modifications in the genetic material and, therefore, it is possible to carry out its cytogenetic detection using biomarkers. Micronuclei (MN) have been addressed in the literature as biomarkers of genotoxic damage. These markers provide information on biological or biochemical changes in a target tissue at early stage, enabling a favorable prognosis. Objective: To compare whether the frequency of MN in active smokers is higher than that in non-smokers. Material and method: The search was performed in the Medical Literature Analysis and Retrieval System (PubMeb), in the Latin American and Caribbean Literature in Health Sciences (LILACS), and in the Scientific Electronic Electronic Library Online (SciELO), for articles published in the last ten years. Randomized clinical trials, with a cross-sectional design, which compared the MN frequency in the oral mucosa of adult smokers and non-smokers, were selected. Results: A total of 52 articles were identified, four of them were removed due to duplicity. From the remaining 48 studies, after reading their titles and abstracts, 14 remained, which had their full texts read. Finally, eight articles remained for the qualitative analysis. Discussion and conclusion: Individuals who use tobacco present genotoxic and cytotoxic damages that interfere in the mitosis process, which leads to MN formation. The hypothesis of smoking as the cause of this genetic alteration is corroborated by the authors when comparing the data obtained in their studies between risk groups and control groups.